The Literature Review in Classic Grounded Theory Studies: - Olavur Christiansen (Grounded Theory Review: An International Journal, 2011)
The place and purpose of the literature review in a Classic (Glaserian) Grounded Theory (CGT) study is to situate the research outcome within the body of previous knowledge, and thus to assess its position and place within the main body of relevant literature. The literature comparison is conceptual, i.e. the focus is on the comparison of concepts. The literature comparison is not contextual, i.e., it is not based on the origin of the data. This, of course, means that the literature comparison has to be made in a selective manner.